Evaluating the Cost Effectiveness of Heifer International Country Programs - Paul Clements (Journal of MultiDisciplinary Evaluation)
Background: In the 1950s and ‘60s cost effectiveness was the primary focus of evaluation of international development aid, but in recent decades this has been increasingly neglected. The most recent decade saw great interest in impact evaluation, but the step from impacts to cost effectiveness was often neglected. This article explains how a multi-year evaluation of a major international NGO that was designed to estimate country program impacts was expanded to include estimates of cost effectiveness.